2004
DOI: 10.1063/1.1839288
|View full text |Cite
|
Sign up to set email alerts
|

Orientation dependence of transverse piezoelectric properties of 0.70Pb(Mg1∕3Nb2∕3)O3-0.30PbTiO3 single crystals

Abstract: Articles you may be interested inStudy on dielectric and piezoelectric properties of 0.7 Pb(Mg1/3Nb2/3)O3-0.3 PbTiO3 single crystal with nanopatterned composite electrode

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 9 publications
0
52
0
Order By: Relevance
“…These modes are (001)/<100>, (001)/<110>, (110)/<001> and (110)/< 1 � 10 >, where the first number indicates the electrode face (perpendicular to poling direction) and the second number is the acoustic wave propagation direction [64]. It has been demonstrated that the highest transverse piezoelectric coefficients are obtained from crystals poled along <110> and vibrated along the <001> direction [64][65][66][67][68], with small signal d 32 coefficients on the order of ~−1500 pC/N and electromechanical coupling factor k 32 ~ 0.90 in PZN-PT, PMN-PT and PMN-PZT crystals.…”
Section: Crystallographic Orientation Dependence Of Propertymentioning
confidence: 96%
“…These modes are (001)/<100>, (001)/<110>, (110)/<001> and (110)/< 1 � 10 >, where the first number indicates the electrode face (perpendicular to poling direction) and the second number is the acoustic wave propagation direction [64]. It has been demonstrated that the highest transverse piezoelectric coefficients are obtained from crystals poled along <110> and vibrated along the <001> direction [64][65][66][67][68], with small signal d 32 coefficients on the order of ~−1500 pC/N and electromechanical coupling factor k 32 ~ 0.90 in PZN-PT, PMN-PT and PMN-PZT crystals.…”
Section: Crystallographic Orientation Dependence Of Propertymentioning
confidence: 96%
“…This singlecrystal PMN-PT possesses a piezoelectric coefficient d 33 < 500 pC/N along the poling direction, and a transverse extension (TE) mode piezoelectric coefficient d 31 ¼ 2300 pC/ N. This type of cut was chosen because of its superior piezoelectric performance. 13 The two faces, with normal vectors parallel and antiparallel to [011], were plated with gold electrodes. The FeGa/PMN-PT heterostructure was positioned between the pole pieces of an electromagnet, so that the direction of the bias magnetic field coincided with the longitudinal direction of the composite.…”
Section: Methodsmentioning
confidence: 99%
“…These modes are ͑001͒ / ͗100͘, ͑001͒ / ͗110͘, ͑110͒ / ͗001͘, and ͑110͒ / ͗−110͘, where the first number indicates the electrode face and the second number is the acoustic wave propagation direction. 5 It has been demonstrated that the highest transverse piezoelectric coefficients are obtained from crystals poled along ͗110͘ and vibrated along the ͗001͘ direction, [5][6][7][8][9][10] with small signal d 32 coefficients on the order of ϳ−1500 pC/ N and electromechanical coupling factor k 32 ϳ 0.90 in PZNT and PMNT crystals.…”
Section: Introductionmentioning
confidence: 99%